Media Religiosity as a Mental Health Stability Factor in the COVID-19 Crisis in Ukraine - Kostruba, Natalia (Journal of religion and health, 2025)
The COVID pandemic has set a precedent where social restrictions and alarming news about the spread and mortality of the virus have kept people in constant emotional tension. Scientists around the world have concluded that society needs psychological support and information assistance to overcome the fear, anxiety, and depression that arise from pandemics. In search of peace, many believers turn to religion. The spiritual institution of the church always takes care of people who need support and hope. However, quarantine restrictions significantly narrowed the church influence on the life of the religious community. At that time, the church significantly expanded its presence in the media space. The phenomenon of media religiosity has emerged as the religion practice using media. The question is, does this new kind of religiosity have an impact on psychological well-being and mental health? So, the purpose of the article is to empirically investigate the relationship and influence of the individual media religiosity level on of the mental health stability indicators. Mental health stability refers to the extent to which individuals reported change in levels of common mental health symptoms (curiosity about life, belonging to a social group, satisfaction with one's personality, etc.). To implement the purpose of the study, we used the questionnaire "Mental health stability - short form" (MHC-SF-UA) adapted by E. Nosenko, A. Chetveryk-Burchak and the Kostruba Questionnaire for Media Religious Individuals (KQMRI). The research was conducted on a convenience sample which consisted of 685 people (181 male and 504 female), average age 22.7 years, from 16 regions of Ukraine. A statistically significant relationship was revealed between: hedonic well-being and the media religiosity cognitive component (r =  − 0.116; p < 0.01); social well-being as a component of mental health stability and the individual's media religiosity conative component (r = 0.078; p < 0.05); mental health stability and cognitive component of a person's media religiosity (r =  − 0.079; p < 0.05). The implemented regression analysis made it possible to identify only one predictor of media religiosity - hedonic well-being (β =  − 0.14, p < 0.05). The results demonstrate that individuals prone to media religiosity have stable mental health, which is most often manifested and supported by social well-being.